The Impact of Population and Family Planning Course on the Knowledge and Attitude of Students towards Contraceptive Methods: a Study on Female Students of Islamic Azad University/Abadan Branch in 20056 - Mahnaz Movaghar; Alireza Sultanian; Mahrokh Movaghar (Kerman University of Medical Sciences, 2007)
Background & Objective : One of the greatest problems of the present century is the uncontrolled increase in population and control of this increase is among the most important priorities of every society if it is to achieve the goals of health and development Proper education via creating a change in individuals attitudes and way of thinking is considered as a basic step in achieving the goals of family planning The aim of this study was to investigate the impact of family planning course presented in universities on knowledge and attitude of students toward contraceptive methods Methods : This quasiexperimental study (beforeafter) performed on 234 female students of Islamic Azad University/Abadan branch who attended the population and family planning course in the first semester of the academic year 20052006 Subjects were selected by nonrandom and convenience sampling Data were collected using a questionnaire distributed once before and once after attending the family planning course Results : According to the results 661% of the students were in the age range of 2024 years 117% were married 177% were employed and 836% were students of associate degree and 164% bachelor degree Mean (±SD) knowledge score of students was 365(±179) before the course that raised to 889(±26) after the course (P=0001) Mean (±SD) attitude score of students before the intervention was 588(±199) that rose to 727(±201) after the intervention (p=0003) Conclusion : Based on the results of this study family planning programs should be based on training since an increase in awareness and attitude of people resulting from efficient educational programs paves the way for using safe contraceptive methods and change of reproductive behaviors